IMPACT OF EXISTING REHABILITATION PROGRAMS ON RECOVERY AND RELAPSE RATES AMONG PATIENTS IN BALOCHISTAN. - Nawaz, S; JAhanzeb, .; Khan, ZU; Khan, HA; Wasay, A; Iqbal, M; Kakar, SU (Biological and Clinical Sciences Research Journal, 2024)
Balochistan faces an increasing substance-use burden and limited rehabilitation infrastructure. Although several government and non-governmental rehabilitation initiatives operate in the province, systematic evidence of their effectiveness, measured by recovery and relapse rates, is sparse. Objective: To evaluate the impact of existing rehabilitation programs on short- and medium-term recovery and relapse rates among patients receiving treatment for substance use disorders in selected districts of Balochistan. Methods: A prospective mixed-methods study was conducted involving 360 patients who entered rehabilitation services between January and June 2023 across six rehabilitation centers (three residential, two outpatients, one community-based) in Balochistan. Quantitative follow-up assessments were conducted at discharge, 3 months, 6 months, and 12 months using standardized measures of substance use (self-report corroborated by urinalysis), psychosocial functioning, and program completion status. Qualitative interviews (n = 36) with patients, clinicians, and program managers explored program components, barriers to sustained recovery, and perceptions of effectiveness. Results: Overall program completion rate was 58% (n = 209). At 12 months post-discharge, the cumulative relapse rate among all participants was 44%. Participants who completed a structured residential program had significantly lower 12-month relapse rates (28%) than those who left early or received minimal outpatient services (62%) (χ² = 46.2, p < .001). Multivariate survival analyses controlling for age, gender, primary substance, comorbid mental-health conditions, and social support indicated that program completion (HR = 0.42, 95% CI [0.31, 0.57]) and access to post-discharge community support (HR = 0.55, 95% CI [0.39, 0.78]) were protective against relapse. Qualitative data identified continuity of care, family involvement, and vocational training as critical components supporting sustained recovery; lack of aftercare, financial stress, and stigma were major drivers of relapse. Conclusion: Existing rehabilitation programs in Balochistan demonstrate measurable benefits, particularly for structured residential programs with integrated aftercare, in reducing medium-term relapse rates. However, high attrition and limited post-discharge support constrain long-term effectiveness. Policy efforts should prioritize scalable aftercare models, family- and community-based support, and quality assurance across rehabilitation services to improve recovery outcomes.